First data on ontogeny of the oribatid mite family Caloppiidae (Acari, Oribatida), with description of juvenile instars of the representative of the genus Zetorchella - Ermilov, Sergey G. (Zootaxa, 2023)
Juvenile instars of Zetorchella arsiensis (Oribatida, Caloppiidae) are described, based on specimens collected from mosses on the swamp at the top of the mountain in Arsi Mountains National Park, Ethiopia. It is the first data on ontogeny for the family Caloppiidae. Main morphological differences between juveniles of Caloppiidae with other families in Oripodoidea are presented.